Relationship between Body Mass Index and Early Mobilization with Serum Production Post Laparotomy Surgery - Merinda, Diajeng; Bahari, Kissa; Bachtiar, Arief; Pertami, Sumirah Budi (Universitas Muhammadiyah Semarang, 2024)
Increased serum production is a complication that often occurs in the period off post laparotomy surgery, with the prolongation of serum production can indicate that there is still a cavity under the post-operative wound filled with serum fluid. Increased serum production causes the drain to take longer to be removed and the hospitalization period is longer, resulting in higher hospital bills. This study aims to analyze the relationship of Body Mass Index (BMI) with serum production post laparotomy surgery and to analyze the relationship early mobilization with serum production post laparotomy surgery. This research design is correlation with cross sectional approach technique and sampling technique using accidental sampling with 18 respondents. The instrument used in this study was an observation sheet. All data obtained tabulated and univariate analysis and bivariate analysis using Pearson correlation performed. The results of the normality test (Shapiro-Wilk) stated that the data normally distributed so that the Pearson correlation test could be carried out using software Statistical Product and Service Solutions (SPSS 20). Correlation test results on BMI variables (ρ = 0.001; r = 0.812), and early mobilization variables (ρ = 0.009; r = - 0.594). Therefore, recommended for implementing nurses, to improve nursing care for patients post laparotomy surgery in the process of emptying serum production. Where in patients who have a high BMI to observe serum production more closely and perform early mobilization training care or provide direction to more often perform early mobilization so that serum production runs out quickly.